2001
DOI: 10.1007/s11745-001-0731-7
|View full text |Cite
|
Sign up to set email alerts
|

Energy value and digestibility of dietary oil containing mainly 1,3‐diacylglycerol are similar to those of triacylglycerol

Abstract: Diacylglycerol (DAG) is a component of various vegetable oils. Approximately 70% of the DAG in edible oils are in the configuration of 1,3-DAG. We recently showed that long-term ingestion of dietary oil containing mainly 1,3-DAG reduces body fat accumulation in humans as compared to triacylglycerol (TAG) oil with a similar fatty acid composition. As the first step to elucidate the mechanism for this result, we examined the difference in the bioavailabilities of both oils by measuring food energy values and dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 27 publications
5
61
1
Order By: Relevance
“…Table 1. Taguchi et al (2001) reported that the calculated energy values were in agreement with the energy values measured by the bomb calorimeter in their study. In our study, the acidolysis reaction was deduced with a tolerable decrease in the caloric value of triolein.…”
Section: Caloric Values Of Structured Lipidssupporting
confidence: 79%
“…Table 1. Taguchi et al (2001) reported that the calculated energy values were in agreement with the energy values measured by the bomb calorimeter in their study. In our study, the acidolysis reaction was deduced with a tolerable decrease in the caloric value of triolein.…”
Section: Caloric Values Of Structured Lipidssupporting
confidence: 79%
“…Taguchi et al, (2001) reported that the energy value of an oil calculated theoretically was in agreement with the energy values measured by a bomb calorimeter. The theoretical energy value of TO was calculated as 39.53 kj·g −1 .…”
Section: Caloric Values Of Structured Lipidssupporting
confidence: 71%
“…First, the energy values for the FA were calculated using the method proposed by Taguchi et al,(2001). Then the heat of combustion of each fatty acid was used to calculate the heat of combustion of each produced TAG.…”
Section: Determination Of Caloric Value Of Structured Lipidsmentioning
confidence: 99%
“…In relation to the fat acylglycerol composition, Murata et al (1997), Taguchi et al (2001) and Murase et al (2005) also did not find differences in the performance of rats fed DAG or TAG oil-enriched diets. In contrast, Meng et al (2004) reported that the weight gain was lower in rats fed a DAG oil-rich diet, while Kamphuis et al (2003) observed a lesser feeling of hunger and appetite in women fed a DAG oil-enriched diet.…”
mentioning
confidence: 77%